2022
DOI: 10.3390/molecules27041207
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Knowledge on Salvia hispanica and Salviae hispanicae semen (Chia Seeds)

Abstract: Chia seeds (Salviae hispanicae semen) are obtained from Salvia hispanica L. This raw material is distinguished by its rich chemical composition and valuable nutritional properties. It is currently referred to as “health food”. The purpose of the present work was to perform a literature review on S. hispanica and chia seeds, focusing on their chemical composition, biological properties, dietary importance, and medicinal uses. The valuable biological properties of chia seeds are related to their rich chemical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 104 publications
0
27
0
Order By: Relevance
“…This ratio has been recommended for the prevention of metabolic diseases. 13,42 We have shown that chia seed administration reversed dyslipidemia and hyperglycemia with no change in the insulin levels. In addition, we have previously demonstrated that the administration of chia seed had an impact on the action of insulin by reversing insulin resistance in SRD-fed rats (euglycemic-hyperinsulinemic clamp).…”
Section: Papermentioning
confidence: 96%
See 1 more Smart Citation
“…This ratio has been recommended for the prevention of metabolic diseases. 13,42 We have shown that chia seed administration reversed dyslipidemia and hyperglycemia with no change in the insulin levels. In addition, we have previously demonstrated that the administration of chia seed had an impact on the action of insulin by reversing insulin resistance in SRD-fed rats (euglycemic-hyperinsulinemic clamp).…”
Section: Papermentioning
confidence: 96%
“…In vitro assays and animal and human models have proved that chia seeds are characterized by neuroprotective, hepatoprotective, anti-inflammatory, and antioxidant properties. [13][14][15][16][17] They are rich in protein, fiber, vitamins, minerals, and antioxidants, and also have the highest α-linolenic acid content (18:3 n-3, ALA). 18,19 Therefore, evaluation of possible functional foods that improve the liver inflammation and endothelial dysfunction could be a strategy to prevent or ameliorate MS-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Salvia hispanica L., popularly known as chia, is an herbaceous annual plant belonging to the Lamiaceae family. Recently, chia seed consumption has increased and gained popularity due to its functional and nutraceutical properties, which greatly bene t human health [13,14]. The high lipid content (especially alpha-linolenic (ω-3) and alpha-linoleic acids (ω-6)) is mainly responsible for the increasing demand for chia seeds in the functional food market [15].…”
Section: Introductionmentioning
confidence: 99%
“…Motyka et al [ 14 ] recapitulate the current status of Salvia hispanica (chia), a plant species of Middle- and South-American origin, in the European health-food industry. The current knowledge about the chemical composition, biological activities, application in the health food and cosmetics industries, and possible applications in phytotherapy and also biotechnological studies of this species are presented in this review.…”
mentioning
confidence: 99%